2022
DOI: 10.3390/nu14051120
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Enteral Nutrition in Critically Ill Patients with COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background: Patients who are critically ill with COVID-19 could have impaired nutrient absorption due to disruption of the normal intestinal mucosa. They are often in a state of high inflammation, increased stress and catabolism as well as a significant increase in energy and protein requirements. Therefore, timely enteral nutrition support and the provision of optimal nutrients are essential in preventing malnutrition in these patients. Aim: This review aims to evaluate the effects of enteral nutrition in cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
1
27
0
7
Order By: Relevance
“…To prevent malnutrition in these patients, immediate enteral nutrition support and the administration of adequate nutrients are crucial [31]. A recent systematic review and meta-analysis evidenced the effectiveness of enteral nutrition in alleviating the mortality risk among COVID-19 patients [31]. In the present study, the "Quick" method and the "Harris-Benedict equation" were the most used by dietitians to estimate the energy requirements of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…To prevent malnutrition in these patients, immediate enteral nutrition support and the administration of adequate nutrients are crucial [31]. A recent systematic review and meta-analysis evidenced the effectiveness of enteral nutrition in alleviating the mortality risk among COVID-19 patients [31]. In the present study, the "Quick" method and the "Harris-Benedict equation" were the most used by dietitians to estimate the energy requirements of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 75%
“…They frequently have considerable increases in their needs for protein and calories, as well as high levels of inflammation, stress, and catabolism [30]. To prevent malnutrition in these patients, immediate enteral nutrition support and the administration of adequate nutrients are crucial [31]. A recent systematic review and meta-analysis evidenced the effectiveness of enteral nutrition in alleviating the mortality risk among COVID-19 patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 hospitalized patients, malnutrition was 42.1%, which increased to 66.7% in patients admitted to the intensive care unit [ 59 ]. A meta-analysis performance by Ojo et al in critically ill patients with COVID-19 showed that early enteral nutrition reduced 11% the risk of mortality (RR: 89, 95%CI; 0.79 to 0.99) and a reduction in SOFA score [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate nutritional treatment in patients with COVID-19 appears to be an important element and would be recommended as a method of primary nutritional support and in critically ill patients [ 26 , 27 ]. Different guidelines state the importance of nutrition risk screening in critically ill patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%